Modelling the Probability of Being Caught (POBC) during Ops Bersepadu for Chinese New Year and Raya Aidilfitri from year 2008 to 2013 at Malaysian Institute of Road Safety Research (MIROS) Kajang Selangor / Asmida Mustafa - Mustafa, Asmida (Faculty of Computer and Mathematical Sciences, 2014)
Malaysia has a high number of road crashes especially during holidays and festive seasons. Integrated traffic enforcement called Ops is conducted as a response but despite efforts, statistics remain high. The effectiveness of Ops is being evaluated and one of the ways is to measure road users’ perception of being caught (POBC). A study using secondary data involving 13,695 respondents was conducted using descriptive, one-way ANOVA, post-hoc and logistic regression analyses. For descriptive analyses, Ops CNY 2012 and Ops Raya 2013 have the highest overall mean score during both Ops. One-way ANOVA resulted that both models during both Ops CNY and Raya were significant. Analysing the post-hoc analysis performed that the POBC during the Ops CNY year 2010 and 2008 were not significantly different with the POBC during Ops CNY year 2012. However, for the year 2013, 2009 and 2011, the POBC were significantly different. Post-hoc analysis for Ops Raya performed that the POBC during Ops Raya 2012 and 2010 not significantly different with Ops Raya 2013. Meanwhile, Ops Raya 2011, 2009 and 2008 were significantly different in theirs POBC. Logistic regression was conducted to analyse the association of chances of being caught with six (6) demographic variables during both Ops. During Ops CNY, only variables age (odd ratio 1.008, p=0.0001) and road type (odd ratio 1.254, p=0.0001) were significant while during Ops Raya, variables gender (odd ratio 1.174, p=0.0100), age (odd ratio 1.011, p=0.0001), road type (odd ratio 1.383, p=0.0001), vehicle frequently used (odd ratio 0.784, p=0.0001) and experienced of being caught (odd ratio 0.808, p=0.0001) were significant. The study revealed that strict and new enforcements should be carried out. Besides that, the authorities should focus more on older road users and road users at federal roads during next Ops CNY as well as female road users, older road users, road users at federal roads, motorcyclists and road users had never being summoned during next Ops Raya. Findings of the study can act as guidelines for programme design and implementations of Ops Bersepadu